An assessment of GHG mitigation potential by electricity expansion planning using LEAP model. (19th October 2021) - Karunanithi, K.; Raja, S.P.; Rayaguru, N.K.; Saravanan, S.; Kannan, S.
The main objective of this paper is to trim down the global warming potential (GWP) which is emitted from various sectors such as domestic, commercial, industry, transportation and agriculture. In this paper, electricity expansion planning problem is analysed for an Indian state, Tamil Nadu, for a period of 30 years from 2019 to 2048 using the LEAP software. Two scenarios, base line scenario and GHG mitigation scenario, are developed. The results show that GHG mitigation scenario can reduce the GWP by 2, 189.2 MMT compared to base line scenario. The cost of avoiding GHGs is estimated as 117.3 USD/tonne CO2 e. Overall, this study's findings provide insights into TN's future energy and highlight potential measures for the creation of a sustainable low-carbon state in India.